Determining Factors In The Decision Of The Bank Of South Sumatra's Gold Installment Customer Babel Syariah - Ririn Dwi Aryanti; Mail Hilian Batin; Tariza Putri Ramayanti (CV. Era Digital Nusantara, 2024)
This study aims to determine whether Digital Marketing, Word of Mouth and quality of Service affect customer decisions on gold installment products at Bank Sumsel Babel Syariah KCP Muhammadiyah Palembang. The population is gold installment customers in Bank Sumsel Babel Syariah KCP Muhammadiyah Palembang as many as 48 customers were taken as a sample. The analysis technique used is multiple linear regression using SPSS with hypothesis testing using t test and F test. The results showed that both partially and simultaneously variable digital marketing, word of mouth and quality of Service affect customer decisions.